INSTALLING TRIM IN A VALVE ASSEMBLY - ROGERS-HEHR, Timothy Daniel; GOSSELIN, Peter David; WALI, Vigneshwar Shaliwan; BETLY, Justin Walter (2024)
A tool configured for use to assemble and install trim into a steam conditioning valve. These configurations can include a device that mounts in place of a bonnet and an actuator that technicians remove from the valve. The device can cantilever the trim assembly, essentially providing a platform on which technicians can slide the trim assembly into the valve body (or out of the valve body) to complete install or repair of the device. As an added benefit, technicians can also use the device to assemble the trim in proximity to the subject valve.